Immunotherapeutic Activities of a DNA Plasmid Carrying the Mycobacterial hsp65 Gene (DNAhsp65) - Silva, Celio Lopes; Malardo, Thiago; Tahyra, Aline Seiko Carvalho (Frontiers in Medical Technology, 2020)
DNA vaccines have become relevant subject matter, and efforts for their development have been increasing due to their potential as technology platforms applicable for prophylactic and therapeutic approaches for infectious diseases and for cancer treatment, allergies, and autoimmune diseases. This review aimed to summarize current knowledge about the plasmid DNA vaccine carrying the mycobacterial hsp65 gene (DNAhsp65), which demonstrates immunomodulatory and immunoregulatory properties of both the innate and adaptive immune systems. The possible mechanisms associated with the modulation and regulatory role of DNAhsp65 in the control of various conditions is also discussed.